A Molecular Targeted Immunotherapeutic Strategy for Ulcerative Colitis via Dual-targeting Nanoparticles Delivering miR-146b to Intestinal Macrophages. (15th November 2018) - Deng, Feihong; He, Shuying; Cui, Shudan; Shi, Yanqiang; Tan, Yuyong; Li, Zhijun; Huang, Chongyang; Liu, Deliang; Zhi, Fachao; Peng, Liang
Abstract: Background and Aims: Macrophages are a promising therapeutic target for intestinal mucosal repair. MiR-146b appears to control macrophage activation and cell proliferation. Methods: By loading miR-146b mimic on mannose-modified trimethyl chitosan [MTC]-conjugated nanoparticles [NPs] [MTC-miR146b], a molecular targeted immunotherapeutic approach was developed to selectively target intestinal macrophages for mucosal regeneration and tumourigenesis in mouse models. Results: We first confirmed that miR-146b expression was significantly enhanced during mucosal regeneration in a murine colitis model. Moreover， after mucosal damage, MTC-miR146b mimic-treated wild-type mice had dramatically restored body weight and mucosal barrier function compared with MTC-NC treated mice. Strikingly, MTC-miR146b mimic oral administration protected miR-146b-deficient mice from dextran sodium sulphate [DSS] injury and the colitis-associated cancer process. Mechanistically, miR-146b strongly inhibited M1 macrophage activation by suppressing the Toll-like receptor 4 [TLR4] signalling pathway, resulting in the repression of the induction of pro-inflammatory cytokines including TNF-α, IL-6, and IL-1β. More importantly, miR-146b overexpression in bone marrow-derived macrophages [BMDMs] in M1 differentiation conditions induced a phenotype similar to M2 macrophages and improved the proliferation of co-cultured colonic epithelial cells via STAT3-dependent IL-10 production. Conclusions: MTC-miR146b should be regarded as an effective candidate for oral delivery and could improve the efficacy of immunotherapies for ulcerative colitis and colitis-associated cancer.